A potential Chinese medicine monomer against influenza A virus and influenza B virus: isoquercitrin - Rongbo Luo; Chaoxiang Lv; Tiecheng Wang; Xiuwen Deng; Mingwei Sima; Jin Guo; Jing Qi; Weiyang Sun; Beilei Shen; Yuanguo Li; Donghui Yue; Yuwei Gao (BMC, 2023)
Abstract Background Influenza viruses, especially Influenza A virus and Influenza B virus, are respiratory pathogens and can cause seasonal epidemics and pandemics. Severe influenza viruses infection induces strong host-defense response and excessive inflammatory response, resulting in acute lung damage, multiple organ failure and high mortality. Isoquercitrin is a Chinese medicine monomer, which was reported to have multiple biological activities, including antiviral activity against HSV, IAV, SARS-CoV-2 and so on. Aims of this study were to assess the in vitro anti-IAV and anti-IBV activity, evaluate the in vivo protective efficacy against lethal infection of the influenza virus and searched for the more optimal method of drug administration of isoquercitrin. Methods In vitro infection model (MDCK and A549 cells) and mouse lethal infection model of Influenza A virus and Influenza B virus were used to evaluate the antiviral activity of isoquercitrin. Results Isoquercitrin could significantly suppress the replication in vitro and in vivo and reduced the mortality of mouse lethal infection models. Compared with virus infection group, isoquercitrin mitigated lung and multiple organ damage. Moreover, isoquercitrin blocked hyperproduction of cytokines induced by virus infection via inactivating NF-κB signaling. Among these routes of isoquercitrin administration, intramuscular injection is a better drug delivery method. Conclusion Isoquercitrin is a potential Chinese medicine monomer Against Influenza A Virus and Influenza B Virus infection.